Populist constitutionalism and illiberal democracies : between constitutional imagination, normative entrenchment and political reality / edited by Martin Belov. - Belov, Martin (Intersentia, 2021)
This book is a topical study of populist constitutionalism and illiberal democracies, exploring their roots in constitutional imagination as well as their normative entrenchment and performance in political reality. It provides insightful analysis of republican constitutionalism, focusing on the role of people in radical democracy and revolutionary constitutional reform. Furthermore, the outlook, adequacy and performance of constitutional principles in times of democratic ruptures are assessed. The contributors examine the rise of populist constitutionalism and the main trends that have led to the current, ongoing crises in liberal democracy. The book includes original analyses of populist constitutionalism from the viewpoint of emotions and constitutional imagination, as well as a special chapter devoted to the challenges posed to constitutional democracy by COVID-19. Combining theoretical contributions, comparative typologies and important case studies, the spread of populism and illiberal democracy in Europe is critically explored. Populist Constitutionalism and Illiberal Democracies is a timely contribution to the lively discussion surrounding constitutional law, comparative constitutional law, comparative constitutionalism and political science regarding the rise and spread of illiberal democracies, authoritarian political regimes and revolutionary, radical democratic and populist constitutionalism. With contributions by Martin Belov (University of Sofia 'St. Kliment Ohridski'), Agnieszka Bien-Kacala (Nicolaus Copernicus University in Torun), Paul Blokker (University of Bologna), Monica Bonini (Università degli Studi di Milano-Bicocca), Carlo Alberto Ciaralli (University 'G. d'Annunzio' of Chieti-Pescara), Eoin Daly (National University of Ireland), Gianmario Demuro (University of Cagliari), Tímea Drinóczi (University of Pécs), Wojciech Engelking (University of Warsaw), Angela Di Gregorio (University of Milano), Marcin Kilanowski (Nicolaus Copernicus University in Torun), Zoltán Pozsár-Szentmiklósy (ELTE Eötvös Loránd University), Przemyslaw Tacik (Jagiellonian University of Kraków), Anna Tarnowska (Nicolaus Copernicus University in Torun), Zoltan J. Toth (Károli Gáspár University), Julia Wesolowska (Jagiellonian University of Kraków) and Wojciech Wloch (Nicolaus Copernicus University in Torun).